IMPLEMENTATION OF AN ONLINE CONCERVATION AREA ENTRY PERMIT (SIMAKSI) SYSTEM IN THE GUNUNG GEDE PANGRANGO NATIONAL PARK AREA 2021 - Fathoni, Muhammad; Basori, Yana FY; Mulyadi, Andi (DIA: Jurnal Administrasi Publik, 2022)
This research is motivated by a problem phenomenon, namely illegal climbers who enter the Gunung Gede Pangrango National Park area without a permit to enter the conservation area (SIMAKSI). In this study using a qualitative research methodology. Data collection techniques used in this study were observation and field studies, interviews, literature studies and qualitative and audio and visual documents. In this study, researchers used triangulation to validate the data, namely source triangulation and technical triangulation. The data analysis used is data reduction, data presentation and drawing conclusions. Based on the results of this study, it shows that the National Park Center has conducted socialization related to the application of the Online Conservation Area Entry Permit (SIMAKSI) policy in the Gunung Gede Pangrango National Park area, so that climbers and the public already know about the application of the Conservation Area Entry Permit (SIMAKSI) policy. Online in the Gunung Gede Pangrango National Park Area. The resources at the Gunung Gede Pangrango National Park Center are sufficient with qualified employees and staff in their respective fields, as well as adequate facilities and infrastructure, such as information Keyword : Implementation, Public Policy, SIMAKSI